Altmetric analysis of the contemporary scientific literature in Endodontology. (6th November 2019) - Kolahi, J.; Khazaei, S.; Iranmanesh, P.; Khademi, A.; Nekoofar, M. H.; Dummer, P. M. H.
Abstract: Aim: To analyse and visualize the knowledge structure of scientific articles in the field of Endodontology with high altmetric attention scores to discover hot topics, active researchers and the journals involved. Methodology: On 5 June 2019, the altmetric database (Altmetric LLP, London, UK) was searched using the titles of 11 endodontic journals. Bibliometric data from endodontic articles and journals with an altmetric score >5 (top 5%) were retrieved from PubMed and analysed using the VOSviewer. Science mapping of articles with an altmetric score >5 at two levels was created: author keywords co‐occurrence and co‐authorship network analysis. Results: Of the 2197 articles in the field of Endodontology identified with altmetrics, 192 had altmetric scores >5 (top 5%). Considering the total mentions amongst all altmetric resources, the Journal of Endodontics had the highest rank followed by the International Endodontic Journal and Australian Endodontic Journal. Twitter was the most popular altmetric data resource followed by patents and Facebook. Meta‐analysis, systematic review and pulpitis were the hot topics. At the author level, Dummer P.M.H had the greatest influence on the network. There was no significant correlation between altmetric score and citations count ( P > 0.05). Mendeley mentions correlated with citations ( P < 0.05). Conclusions: Overall, the altmetric scores of topics within Endodontology were low, possibly due to the specific and specialized nature of the specialty, as well as the difficulty members of the public probably have in understanding endodontic research. Journals and researchers with a focus on Endodontology would have more influence if they were to set‐up their own social media profiles and thus enhance their visibility and social impact by immediately sharing research findings and communicating with their network and audience.